Mulheres Ideais: Uma análise do processo de construção e de manutenção das representações sociais das esposas de pastores batistas de Curitiba, PR, - Rocha, Fernanda (2008)
There is a figure, not yet considered for the Religion Science, in the middle of institutions, church activities as prayer meetings, worship celebrations, choir, children ministries, home care, sons, daughters and husbands: Baptist pastor’s wife. The main target of this research is to analyze the process of these women to build and to keep their social representations. In order to that, in the first chapter we identify and analyze the gender social representations that are a reality in the structure and in the daily basis in baptist churches, and their reflexions in the elaboration and conservation of the profile of pastor’s wives. In the second chapter we make and analysis of the power and roles of the theological and ministerial teaching institutions in the baptist denomination, as ways to idealize, build and keep the profile of pastor’s wives. In the third chapter we investigate about how a pastor’s sife can handle the transit in between the public and private spaces —gathered one to another—, and in the ways in which the institutional power acts in these places. In order to do that, we use the etnographic method, watching the selected baptist churches, aplying the question forms to the church members, institution leaders and students from the Faculdade Teológica Batista do Paraná —FTBP—, an making interviews with pastors and their wives. The theories in Social and Religion Sciences will provide us the theoretical support that we need to develop the text and to analyze the empiricist data.(AU)